Desenvolvimento de peças moldadas em polímeros para produtos da indústria de balas de goma - Oliveira, Everaldo Fernandes de (2015)
This work aimed at studying and establishing procedures for the manufacture of dies and parts in polymers, verifying the impact of temperature variation in hardness of Shore "A" and the surface quality of the material used in the manufacture of parts in polyurethane (PU) forthe production of jelly beans. Conventionally industries have the option to acquire parts in aluminum or cast developed by equipment suppliers. However, those are standard parts and belong to the portfolio ofproducts from equipment manufacturers and may be marketed without any distinctiveness, so they are not interesting options for industries which have their focus on innovative and unique products. Furthermore, the materials used for manufacturing parts are generally of difficult hygiene process offering no guarantee on Food Safety due to the risk of contamination. The need of importation also generates high cost and long period for shipping the material which can also be damagedduring the logistics of importing. It is common toget surface defects on the plaster and kneading pieces in aluminum parts. Such problems affect the quality of the final product and do not meet the requirements of the industry. As a result of this work we found out that the forged machine dies in polyurethane plates gota clear-cut appearance and great finish. Furthermore, it was ascertained that is not interesting to usevacuum in the production of the silicone dies but positive pressure in order to avoid the incidence of bubbles which impair the finish of the polyurethane parts produced from this matrix. It was also proven that the room temperature has a significant influence in the curing process time, finish quality and hardness of the polyurethane pieces produced by the casting process in a negative silicone matrix. As result, it is noteworthy that the development of the procedure as wellas the good performance of partsfor molding candies allows the company to break the third-party dependency relation for the production of parts and molds ensuring confidentiality in developing new products and reducing costs.